Using personal reprint management software to teach information management skills for the electronic library. - Owen DJ (Medical Reference Services Quarterly, 1997)
The growing electronic library now provides researchers, students and clinicians with ready access to a wide range of useful electronic information sources which can augment, and increasingly replace, the traditional print versions. As a result of this, medical researchers and health professionals are turning to librarians for guidance in the effective organization, and manipulation of personal information collections. Many library instruction programs have responded to this need by providing instruction in information management, including the use of microcomputer-based personal reprint management applications. The focus of this paper is how a class centered around this software can be an ideal format for introducing more users to much broader issues of personal information management skills in the electronic era.